Assessing the Readiness for Transformation of Government Organizations Using the Dice Framework (Case in the Center for Mobilizing Teachers in East Java Province) - Mohamad Nasikh Lil Sidi (UNIVERSITAS PAKUAN, 2023)
Bureaucratic reform is one of the government's steps to develop a change strategy for government organizations in providing accountable services to the public with various innovations and creativity through ZI-WBK Development. Government organizations must be able to carry out organizational transformation so that they are able to adapt and become more agile in facing various challenges in the development of technology and information. In carrying out organizational transformation, strategic steps are needed starting from preparation to implementation to achieve organizational transformation success. The readiness of the transformation of government organizations can be seen from the hard side of change and the soft side of change. Government organizations can focus on hard factors of change using the DICE framework. Through this framework, it will be known the possibility of the success of the organizational transformation process carried out and will find various potential obstacles and parts that need to get the focus of attention to be addressed immediately and efforts to improve their handling. By knowing from the start the things that are the main focus of change and various things that are potential obstacles, government organizations can anticipate and develop the right strategy in the process of organizational transformation.